TUMA’NINAH DALAM AL-QUR’AN SEBAGAI LANDASAN PENDIDIKAN JIWA: KAJIAN TAFSIR TARBAWI - Isma Muhsonah; Iffa Mutmainah; Irfa Afrini (Dirasat: Journal Islamic Studies, 2026)
Mental health has become a global issue that is receiving increasing attention across various levels of society. Modern clinical psychology has contributed significantly to the understanding and addressing of various mental disorders through scientific approaches, behavioral therapy, and medical interventions. However, within Muslim societies, these approaches are not considered fully capable of responding to the needs of the human soul in a holistic manner, because aspects of faith and spirituality are often not placed at the center of mental development. This qualitative descriptive literature review positions the Qur’an as the primary source, particularly verses related to the concept of tuma’ninah. Secondary sources include authoritative works of Qur’anic exegesis and tafsir. Based on a tafsir tarbawi analysis of Qur’anic verses, tuma’ninah represents the true tranquility of the soul rooted in faith, dhikr, righteous deeds, and spiritual closeness to Allah. Tuma’ninah is not merely a temporary emotional condition but an inner stability that arises through an integral process of soul education, including the strengthening of creed, tazkiyatun nafs, spiritual formation, and comprehensive psychological management. Thus, tuma’ninah serves as an indicator of the success of Qur’anic education for the soul.